Sentiment Analysis of TikTok Comments on the Weakening of the Rupiah Exchange Rate as an Indicator of Public Perception of Financial Risk - Baiq Wira Hartati; Ahda Sabila Wulandari; Risma Anggraeni; Nur Asmita Purnamasari (Kiswah Institute, 2026)
The weakening of the rupiah against the U.S. dollar is an economic issue that can influence the public’s perception of financial risk. The social media platform TikTok has become one of the channels the public uses to express their opinions on current economic conditions. This study aims to analyze the sentiment of TikTok users’ comments regarding the weakening of the rupiah as an indicator of the public’s perception of financial risk. The method used is text mining with a Lexicon-Based Sentiment Analysis approach. The research data consists of 163 TikTok comments discussing the weakening of the rupiah exchange rate. The analysis stages include data preprocessing, word cloud visualization, and sentiment classification into positive, neutral, and negative categories. The results show that negative sentiment dominates at 56.44%, followed by neutral sentiment at 38.65%, and positive sentiment at 4.91%. The most frequently occurring words include “Prabowo,” “MBG,” “rupiah,” “president,” “rise,” and “dollar.” The dominance of negative sentiment indicates public concern regarding the impact of the weakening rupiah, such as rising prices, declining purchasing power, and economic uncertainty. The research results suggest that social media sentiment analysis can serve as an early indicator for understanding the public’s perception of financial risks in real time.